2014
DOI: 10.1089/ars.2013.5524
|View full text |Cite
|
Sign up to set email alerts
|

Rho/Rho-Associated Coiled-Coil Forming Kinase Pathway as Therapeutic Targets for Statins in Atherosclerosis

Abstract: Significance: The 3-hydroxy-methylglutaryl coenzyme A reductase inhibitors or statins are important therapeutic agents for lowering serum cholesterol levels. However, recent studies suggest that statins may exert atheroprotective effects beyond cholesterol lowering. These so-called ''pleiotropic effects'' include effects of statins on vascular and inflammatory cells. Thus, it is important to understand whether other signaling pathways that are involved in atherosclerosis could be targets of statins, and if so,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 181 publications
4
65
0
Order By: Relevance
“…45 Indeed, recent studies demonstrated that ROCK inhibition by statins could lead to improved endothelial function and decreased atherosclerosis. 187 Rho-kinase plays a crucial role in the pathogenesis of coronary artery spasm. 2 Coronary spasm plays an important role in variant angina, myocardial infarction, and sudden death.…”
Section: Rho-kinase In Vascular Diseasesmentioning
confidence: 99%
“…45 Indeed, recent studies demonstrated that ROCK inhibition by statins could lead to improved endothelial function and decreased atherosclerosis. 187 Rho-kinase plays a crucial role in the pathogenesis of coronary artery spasm. 2 Coronary spasm plays an important role in variant angina, myocardial infarction, and sudden death.…”
Section: Rho-kinase In Vascular Diseasesmentioning
confidence: 99%
“…2,3 ROCKs are serine/threonine kinases of 160 kDa, and are one of the downstream targets of RhoA that have diverse cellular functions. 4,5 They are composed of a kinase domain, followed by a coiled-coil-forming domain that contains a Rho-binding domain, and a cysteine-rich domain located within a pleckstrin-homology domain. There are two isoforms, ROCK1 and ROCK2, that share high homology (65% in the total amino-acid sequence, 92% in the kinase domains).…”
mentioning
confidence: 99%
“…These include the cellular migration, proliferation, fibrosis and contraction of VSMCs; endothelial cell dysfunction mediated by decreased NO bioavailability; migration of macrophages and their transformation into foam cells; and hypertrophy and deleterious remodeling of the myocardium. 4,5 Of all these activities, the effects on the contraction of VSMCs have been the most intensively investigated in vitro and in vivo. In experimental systems, the pathologically activated Rho/ROCK pathway has been shown to phosphorylate the myosin binding subunit of the myosin light chain (MLC) phosphatase, creating an imbalance between MLC phosphatase and MLC kinase that in turn leads to a calcium ion-independent hypercontraction of VSMCs.…”
mentioning
confidence: 99%
“…Further to the role of statins in Rac1-mediated regulation of vascular and myocardial redox state, Sawada and Liao (8) focus on the role of HMG-CoA reductase inhibition in the regulation of Rho/ROCK pathway in atherogenesis (Fig. 1).…”
mentioning
confidence: 99%
“…1). ROCKs play an important role in cellular apoptosis, growth, metabolism, and migration via the control of the actin cytoskeletal assembly and cell contraction (8). Importantly, there is a cross talk between NO and Rho/ROCK signaling in the vascular wall, as endothelial-derived NO diffuses into the adjacent vascular smooth muscle cells (VSMCs) of the blood vessels, activates soluble guanylate cyclase, stimulates the formation of cGMP, and subsequently activates cGMPdependent protein kinase (cGK).…”
mentioning
confidence: 99%